Agroecology and the metropolitan biopolitics of food in Cape Town and Johannesburg. Issue 1 (7th June 2021) - Kroll, Florian
Abstract: As urban food systems erode the ecological foundations of society, researchers advocate multi‐level and adaptive governance to promote transitions toward sustainability. Agroecological discourse proposes transition to resilient, localized, and democratic city–region food systems, but neoliberal interpretations subvert radical aspirations. In the South African metropoles of Johannesburg and Cape Town, the governance terrain entails a concentrated industrial food system providing large, impoverished populations with unhealthy food derived from monocultures and transported along global value chains. Governing these urban food systems toward agroecological transition requires engagement with state governance mechanisms and rationalities. Considering state capabilities to promote agroecological transitions, the paper shows that fragmented institutional structures, policy patchworks, intersecting logics of control, and divergent ideologies constitute an ambiguous governance terrain posing major hurdles to transition. For metropolitan states to muster the will and assemble means for deep transformation of food systems and dominant state rationalities, a compelling alternative narrative must emerge. This requires persistent strategic engagement between officials and agroecological movements. To cultivate fertile political ground for seeds of deep, just transitions to take root, agroecology movements must grasp the nettle of metropolitan state capabilities. Core Ideas: Metropoles in the Global South are sites of struggle for agroecological transition. South African cities entail large, impoverished, food insecure populations. Hybrid metropolitan food systems are dominated by a corporate–industrial core. Deep, just transitions depend on state will and means to govern food systems Agroecology must engage the incoherent metropolitan will and means for transition.